A study on the parameters influencing flexural bond stress in reinforced concrete. (November 2018) - Siempu, Rakesh; Pancharathi, Rathish Kumar
Abstract: The bond in reinforced concrete is responsible for the safe transfer of forces between reinforcement and the surrounding concrete ensuring strain compatibility and composite action. The bond stress under flexure i.e. bending is of importance to researchers as it resembles the actual state of stress in a structural member. Full scale beam tests were conducted to determine the bond stress under flexure. The major parameters that influence the performance of bond in reinforced concrete are addressed in this investigation. These are water-binder ratio (w/b = 0.5, 0.4 and 0.3) and diameter of bar (d = 10, 12 and 16 mm). Also, the effect of variation of cover to reinforcement on the bond strength was investigated. The specimen and test procedure adopted were as per the specifications of Rilem-Fip-Ceb (1973). From the experimental results, it was concluded that with increase in the concrete strength the bond stress increased. The reduction in bond stress was observed with the increase in bar diameter. The flexural bond stress results were compared with the results of previous work (based on pull-out tests) and found that the flexural bond stress results are lower than the corresponding pull-out tests results. A comparison with the literature models to predict the bond stress was also carried out.